Age Peculiarities of Communicative Competence Development in Ontogenesis - Halapchuk-Tarnavska, Olena (East European Journal of Psycholinguistics, 2014)
The article reveals the age peculiarities of development of communicative competence in ontogenesis. The notion of communicative competence is defined. Formation and development of conversational competence of a child is influenced by family, school and peers. Communicative competence presupposes four types of skills and knowledge: grammar, sociolinguistic, discoursive and strategic. Strategic communicative competence of children is analyzed in the symmetrical (in which age, social status and social role of interlocutors are equal) and asymmetrical speech situations of convince (in which communicants are not equal in the abovementioned parameters). Strategy is understood as speech/ not speech actions that are aimed at reaching communicative goal and are flexible in the asymmetrical speech situations and both soft and flexible in the symmetrical speech situations. The strategy to persuade the interlocutor is realized by the age-neutral tactic of repetition and tactic of refuting; age-preferential tactics of counterbalancing, "catching" the key word, prohibition and using conditionals is utilized by adults in asymmetric situations. References Ackerman, B. (1978). Children’s Understanding of Presuppositions of «Know» and Other Cognitive Verbs. Child Development: 49, 311–318. Astington, J., Harris P., Olson D. (1988). Developing Theories of Mind. Cambridge : CUP. Binchy, M. (1995). The Glass Lake. New York: Dell Books. Carnegie, D. (1981). How to Win Friends and Influence People. Retrieved 14.04.2014 from http: //ramonthomas.com/downloads/How_To_Win_Friends_And_Influence_People.pdf Dijk, T. van (1989). Jazyk, poznanie, kommunikatsia [Language, Cognition and Communication]. Moscow: Progress. Flagg, F. (1992). Fried Green Tomatoes at the Whistle Stop Café. London : Vintage. Grice, H. (1975). Logic and Conversation. Syntax and Semantics, 3, 41−58. Grimm, H. (1975). Analysis of Shortterm Dialogues in 5−7 Year Olds. The Third International Child Language Symposium. London. Grisham, J. (1993). Client. London: Arrow Edition. Halapchuk, O. (2000). Vikova Diferentsiatsiya Stratehiy i Taktyk Diskursu v Suchasniy Anhliyskiy Movy [Age Differentiation of Discourse Strategies and Tactics in English]. Ph.D. thesis. Kharkiv: Kharkiv National University. Helfric, H. (1979). Age Markers in Speech: Social Markers in Speech. Cambridge: CUP. Lee, H. (1977). To Kill a Mockingbird. Kyiv: Dnipro Publishers. Leontyev, A. (1972). Problemy Razvitiya Psykhiki [Problems of Psyche Development]. Mosсow: Moscow State University. Leontyev, A. (1999). Osnovy Psykholingvistiki [Basics of Psycholinguistics]. Mosсow: Smysl. Luria, A. (1979). Yazyk i Soznanie [Language and Consciousness]. Mosсow: Prosveschenie. McNeil, D. (1996). Developmental Psycholinguistics. Genesis of Language. Cambridge: CUP. Shatz, M., McClosky, L. (1984). Answering Appropriately: Discourse Development: Progress in Cognitive Developmental Research. New York: Springer Verlag. Steel, D. (1995) Accident. New York: Dell Books. Swain, M. (1984) Large-scale communicative testing: A Case Study. Reading Mass.: Addison Wesley. Tannen, D. (1982). Oral and Written Strategies in Spoken and Written Narratives. Language, 58, 1−21. Troyanov, I. (1989). Lichnostnye Strategii Obosnovaniya v Diskurse [Personal Argumentation of Choosing Strategies in Discourse]. Kalinin: Kalinin State University.